Highly Pure Nanostructured Copper Oxide Thin Films by Dual Magnetron Sputtering - Basima S Dawood AL – Badri (Academia Open, 2025)
General Background: Copper oxide (CuO) is a promising semiconductor due to its excellent optical, electrical, and catalytic properties, making it suitable for applications in photovoltaics, sensors, and catalysis. Specific Background: However, the fabrication of highly pure, single-phase nanostructured CuO thin films remains challenging, as many synthesis methods produce mixed phases of Cu, CuO, and Cu₂O, reducing material performance. Knowledge Gap: Few studies have systematically optimized sputtering parameters—particularly gas ratios and electrode spacing—in dual magnetron sputtering systems to precisely control phase purity and morphology. Aims: This research aimed to synthesize and characterize highly pure nanostructured CuO thin films using a home-made dual magnetron sputtering system by adjusting argon-to-oxygen ratios and electrode distances. Results: The films prepared at an Ar:O₂ ratio of 1:1 and 2.5 cm electrode spacing exhibited a single-phase CuO confirmed by XRD, with particle sizes decreasing from 44.99 nm to 19.68 nm as oxygen increased. AFM and FE-SEM showed enhanced surface roughness, while UV-Vis analysis revealed a 1.3 eV band gap suitable for solar absorption. Novelty: This study demonstrates a refined sputtering configuration enabling reproducible synthesis of pure CuO nanostructures. Implications: The findings support improved CuO thin-film production for solar energy and optoelectronic devices.Highlight : CuO thin films were synthesized using dual magnetron sputtering with controlled Ar:O₂ ratios. Single-phase CuO was obtained at 1:1 gas ratio and 2.5 cm electrode distance. The films showed high optical transmittance and a 1.3 eV band gap suitable for solar energy use. Keywords : Copper Oxide, Magnetron Sputtering, Nanostructured, Synthesis, Thin Film